The relationship of featural writing skills with the other aspects of early writing in preschool children - Sanchez, R. D. (Compendium of Human Ecology Researches in the Philippines, 2003)
The study was a descriptive correlational study of early writing attempts of 36 three to five-year old children and the relationship of featural writing skills with the other aspects of early writing. After four writing events sessions, three raters scored each child in the different aspects using the Early Writing Attempts Checklist in Medrano (1997). Scores were averaged and results revealed that in the entire sample, 33% were in the ideographic stage, 31% in symbolic stage, 28% in invented spelling and 8% in conventional writing stage. Sixty-one percent showed correct knowledge in directionality, 44% mixed upper and lower cases in using of letters, 97% had no knowledge in spacing, 72% read in monologues, 61% showed pseudoconceptual thinking and 97% wrote independently. Using Spearman rho formula, it was found out that featural writing skill was significantly correlated with directionality; use of letter cases; reading of written text; cognitive attention in written composition and spacing. There was negligible correlation, however, between featural writing skills and process of generating an output.